Adult Age in Marriage in Indonesia (Theoretical Study of the Application of the Lex Posterior Derogat Legi Priori Principle) - Taufik Hidayat Simatupang (Jurnal Penelitian Hukum De Jure, 2021)
The problems to be answered in this research are, first, how is the regulation of Islamic family law and marriage in Indonesia, second, how is underage marriage and legal protection for children, third is how to apply the lex posterior derogat legi priori principle in determining the adult age for marriage. The research method used is normative juridical research with a statute approach which was analyzed using statutory principles. The results of the research concluded that Islamic family law cannot be separated from the history of the legal system in Indonesia from the time of Dutch colonialism to the present which involved three parties, namely the interests of religion, the state and women. Underage marriage is influenced by economic problems, parental coercion and community culture. Based on the lex posterior legi priori principle, the age limit of a child must be seen in the context of what the maturity measure is to be used. If the maturity is for a marriage, then the adult age limit is 19 years, for both women and men. Although in the future it is suggested that further research is needed regarding the financial maturity of men who are married at the age of 19.